Periodic Steady-state Solutions of a Liquid Film Model via a Classical Method. Issue 1 (1st March 2018) - Alhasanat, Ahmad; Ou, Chunhua
Abstract: In this paper, periodic steady-state of a liquid film flowing over a periodic uneven wall is investigated via a classical method. Specifically, we analyze a long-wave model that is valid at the near-critical Reynolds number. For the periodic wall surface, we construct an iteration scheme in terms of an integral form of the original steady-state problem. The uniform convergence of the scheme is proved so that we can derive the existence and the uniqueness as well as the asymptotic formula of the periodic solutions.